PENGEMBANGAN MODUL TERAPI AL-QUR’AN SURAH THAHA AYAT 25-28 UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA SAAT BERBICARA DI DEPAN UMUM DI SMP NEGERI 8 PEKANBARU - Pinda Mayola; Zulfan Saam; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract : This study determines to develop a therapy module of Al-Qur'an Surah Thaha Verses 25-28 to increase students self-confidence when speaking in public. The type of this study is Research and Development (R&D) which is limited to a few stages by conducting research but not continuing with field testing. In developing a better module, this research carried out a validation test for two areas of expertise, which are material experts and interpreters. The data collection techniques in this study used study of literature and validation questionnaires. The result of this research is that the compiled module of Al-Qur'an Surah Thaha Verses 25-28 to increase students self-confidence when speaking in public divided into five guidance activities with a total reading duration of ± 45 minutes. The result of the module validation test as a whole based on the material and interpretation aspects shows that the assessment obtained an average value of 83.47% declared